The Economic Function of a Stock Exchange - Schwartz, Robert A (Springer, 2015)
In recent years, exchanges on both sides of the Atlantic have been extensively reengineered, and their organizational structures have changed from non-profit, membership organizations to for-profit, demutualized organizations. Concurrently, new alternative trading systems have emerged and the traditional functions of broker/dealer firms have evolved. How have these changes affected the delivery of that mission? How has the efficiency of capital raising in the IPO market been impacted? These are among the key questions addressed in this book, titled after the Baruch College Conference, The Economic Function of a Stock Market. Featuring contributions from a panel of scholars, academicians, policymakers, and industry leaders, this volume examines current issues affecting market quality, including challenges in the marketplace, growth opportunities, and IPO capital raising in the global economy.